Mengkritisi HP-3 Perspektif Konstitusi dan Pemberdayaan Rakyat (Kontribusi Teori Sosiologi Membaca Putusan Nomor 3/PUU-VIII/2010) - Tobroni, Faiq (Jurnal Konstitusi, 2012)
This paper aims to criticize the contradictions of Rights of Coastal Management (HP-3) against the 1945 Constitution and the spirit of community empowerment. HP-3 became norm of the procedures for permitting management of Coastal and Small Islands Resources (SDP-PPK) as regulated in Law Number 27 Year  2007.    The recent study collects data through literature approach and analyzes them through qualitative methods. The findings are as follows. HP-3 is contrary to the 1945 Constitution. Unconstitutionality of HP-3 is caused by changing  SDP-PPK  from being common property right to be property right and ignoring alignments    to vulnerable populations (indigenous and traditional fisherman). The principle of empowerment that has significant power to revive the spirit of the constitution in HP-3 is improvement of capabilities and power for vulnerable people. These steps must be taken by creating articles that contain affirmative action for vulnerable people.